Seismic Risk Assessment of a 2-storey Steel-sheathed CFS Building Considering Different Sources of Uncertainty. (November 2018) - Jiang, Liqiang; Ye, Jihong
Abstract: In this paper, four types of uncertainties are considered for seismic risk assessment of steel-sheathed CFS structures. The record-to-record uncertainty is examined by using 40 ground motions selected from SAC project. The structural uncertainties are modeled by 6 random variables by using Latin hypercube sampling method (LHS). The uncertainty in defining performance limits is introduced and determined by statistical analyses of test results. Besides, epistemic uncertainty is considered in three levels: small, moderate and high levels. The seismic risks of a 2-story typical steel-sheathed CFS building are investigated by considering different sources of these uncertainties, and their effects on the building are discussed. The results shown that the uncertainty in defining performance limits has significant impact on the risk of the building which cannot be neglected. It is found that the increment on the probability in 50 years of the building with considering the structural uncertainty is <8.8%. It is suggested that the structural uncertainty could be taken into account in the uncertainty in defining performance limits because these uncertainties are generated from the structural system, and the integrated logarithmic standard deviation dispersion (LSD) is proposed as 0.41 for the steel-sheathed CFS building. The collapse probability in 50 years of the building with considering these four types of uncertainties is 1.84 to 4.56 times of the value with solely considering the record-to-record uncertainty. Highlights: Seismic risks are quantified for a low-rise steel-sheathed CFS building. The uncertainty in defining performance limits is introduced and determined. The structural uncertainties are modeled by generating random realizations. Probabilities of the building are assessed with different sources of uncertainty.